(untitled) (Experimental biology, 2016)
To assess the biotechnological potential of native microorganisms adapted to water and soils of Kazakhstan area of the Caspian Sea, microbiological tests of sea water in selected areas of the peninsula Buzachi, adjacent to oil fields "Kalamkas" and "Karajanbas" were conducted. The number of bacteria in water samples determined by the growth of microorganisms in the MPA medium, of microscopic fungi and yeasts - on Saburo medium, the number of actinomycetes and bacteria - on Chapek medium. Registration and allocation of oil-oxidizing microorganisms conducted using local oil fields. It was found that the oil-oxidizing bacteria are widely distributed in the study area. Dominating are oil-oxidizing bacteria. Number of micromycetes, actinomycetes and yeast in sea water area are lower on several orders of magnitude.